2007
DOI: 10.1007/s10895-007-0242-9
|View full text |Cite
|
Sign up to set email alerts
|

Study of Structural and Photoluminescent Properties of Ca8Eu2(PO4)6O2

Abstract: In this work it is presented for the first time the nanostructured hydroxyapatites doped with 0.5, 1.0 and 2.0 wt% of Eu(3+) prepared at room temperature by the mechanical alloying technique. X-ray diffraction powder (XRD), infrared (IR) and Raman scattering spectroscopy, scanning electron microscopy (SEM), microhardness measurements as well as luminescent data of Eu(3+) were used to investigate the structural and optical properties of these nanomaterials. The electrical and dielectrical analyses were used wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 36 publications
0
18
0
1
Order By: Relevance
“…Patients in this study were stratified by their baseline statin or dose/type used at the time of hospitalization (that is, low-, intermediate- and high-potency statin), since different types and doses of statins are known to vary with respect to their LDL-C-lowering efficacies [25]. Furthermore, while statin therapy is generally well tolerated when used at moderate doses, the risks of liver- and muscle-related AEs are known to increase with higher statin doses [26, 27]. As a result, patients were stratified by statin potency tertiles to allow for balanced between-group comparisons of efficacy, safety and tolerability endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in this study were stratified by their baseline statin or dose/type used at the time of hospitalization (that is, low-, intermediate- and high-potency statin), since different types and doses of statins are known to vary with respect to their LDL-C-lowering efficacies [25]. Furthermore, while statin therapy is generally well tolerated when used at moderate doses, the risks of liver- and muscle-related AEs are known to increase with higher statin doses [26, 27]. As a result, patients were stratified by statin potency tertiles to allow for balanced between-group comparisons of efficacy, safety and tolerability endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…9, usually confirms the formation of apatite [35]. Bands observed at 564, 565, 601, 602 cm -1 are attributed to asymmetric and symmetric bending of PO 4 3-(m 4 ). Bands observed at 965, 966 cm -1 are assigned to symmetric stretching of PO 4 3-(m 1 ).…”
Section: Ft-ir Studymentioning
confidence: 72%
“…2 A 1g (G), 2 T 1g (G) and 2 A 1g (F) respectively. In O h symmetry theoretically the ratios of energies of transitions 4 T 1g (F) ? 4 A 2g (F): m 2 and 4 T 1g (F) ?…”
Section: Optical Absorption Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Europium in its trivalent state is one of the most studied among rare earth ions by luminescence spectroscopy due to the simplicity of its spectra and wide application as red phosphor in color TV screens. This ion has also attracted significant research attention due to its potential application as biological sensors, phosphors, electroluminescent devices, optical amplifiers or lasers when used as doping in a variety of materials 10,11 . Dutta et al 12 showed Indium hydroxides with different morphology such as spheres 13 , flowers 14,15 , cubes [16][17][18][19][20][21][22] , rods 23,24 , etc., have been synthesized by several synthesis methods.…”
Section: Introductionmentioning
confidence: 99%